Synergies between Land Degradation Neutrality goals and existing market-based instruments. Issue 94 (April 2019) - Baumber, Alex; Berry, Emily; Metternicht, Graciela
Highlights: Offsets and public-private partnerships have been explored to promote LDN. Synergies exist with between LDN goals and existing market-based instruments. Relevant schemes cover carbon, biodiversity, watershed protection and bioenergy. Mandates, tax breaks and multifunctional indices could be adapted to integrate LDN. Abstract: Since the concept of the Land Degradation Neutrality (LDN) emerged in global policy discourse, a key point of contention has been the development of market-based instruments to promote the LDN agenda. Much of this discussion has focused on the use of LDN-specific offset mechanisms and private-public partnerships. However, there is also an opportunity to capitalise on the synergies that exist between LDN objectives and those of existing market-based instruments that have previously been developed for carbon, biodiversity, bioenergy and in other contexts. LDN objectives could be integrated into such schemes through targeted eligibility rules and certification schemes, supporting methodologies, adaptations to multifunctional indices used in auction-based approaches and the restructuring of mandates, tax breaks and feed-in tariffs for bioenergy and other products.